City of darkness, city of light : émigré filmmakers in Paris 1929-1939 - Phillips, Alastair (Film culture in transition., 2004)
A ground-breaking study of the cinematic representation of Paris in the films of migr filmmakers who made it their first refuge from Hitler's Germany.